Implementation of a Series Resonant Inverter to Improve Fluorescent Lamp Efficiency - Bayona Navarro, Jhon Fredy; Vera Vera, Jhon Edwin; Gelvez Garcia, Nancy Yaneth (TECCIENCIA, 2016)
The purpose of this paper is shows some design parameters of a series resonant inverter (SRI) half-bridge configuration applied in lamps, this circuit is novel compared with the inverter resonant in series-parallel circuit (SPRI), in actuality the resonant inverters SPRI are very used to supply the power needed in fluorescent lamps, . In order to analyze the behavior and efficiency, is implemented a circuit SRI to supply the energy needed in a 32 W fluorescent lamp. The final results show a better efficiency with the proposed circuit compared to a classical SPRI.